Linearization of the Sobolev and Babeyko’s formulae for transformation of P-wave velocity to density in the Carpathian-Pannonian Basin region - CSICSAY, Kristián; BIELIK, Miroslav; MOJZEŠ, Andrej; SPEVÁKOVÁ, Eva; KYTKOVÁ, Bibiána; GRINČ, Michal (Contributions to Geophysics and Geodesy, 2012)
The initial density model has to be based on a reasonable geological hypothesis and while the modelling process is non-unique, one of the interpretation aims is to define the robust parameters of the model. It is important at this stage to integrate the seismic and gravity data. One of the possibilities how to integrate these data is transformation of the seismic velocities to densities. The Sobolev and Babeyko’s formulae belong to the most available relationships for this transformation. They are very complex and rigorous taking into account the PT conditions. On the other hand its application is relatively complicated. Therefore the main goal of the paper is to try to determine more easily the formula for transformation of the seismic velocities to densities. Based on the analysis of the results obtained using the Sobolev and Babeyko’s formula on real data, we found out that in the Carpathian-Pannonian Basin region this formula can be transformed to simpler linear velocity–density relationship with required accuracy.